The influence of gender and position on occupational stress in educators - Senthilkumar, R.; Indira, K. (AIP conference proceedings, 2023)
Participants should be able to complete their respective responsibilities more effectively and efficiently thanks to the fast advancement of computer technology. Nonetheless, some instructors have encountered a roadblock about their use of digital technology in the classroom. This cognitive concept also demonstrates technostress as a result of their unfavourable beliefs and reluctance to digital technology adoption. The goal of this study is to assess the social cognition theory is true standpoint on the link between individual views of cloud computing adoption, heavy workloads, job insecurity, and perceived stress as evidenced by emotional and behavioral reactions. A sample of 152 technical college instructors from a specified region in Chennai were surveyed. People who have high levels of intellectual confidence in digital technology would have less cognitive dissonance without fear of increased workload or job instability as a result of their lack of technological effectiveness.